2008
DOI: 10.1353/hpu.0.0016
|View full text |Cite
|
Sign up to set email alerts
|

The Costs of Recruitment and Retention of Women from Community-Based Programs into a Randomized Controlled Contraceptive Study

Abstract: Two hundred and forty five women were identified in recruiting and enrolling 103 study participants involving 1,232 contact-attempts. Self-referral had the highest ratio of referrals to enrollees (55.6%), while this ratio was the lowest for community outreach (33.3%). Retention activities succeeded in maintaining over 90% of the sample. Ninety-two percent of English-speaking participants completed the study versus 79% of Spanish-speaking participants. The time expenditure per enrollee was 10.4 hours for recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…While extensive follow-up may improve participant retention, it can also be time consuming, costly, and may contribute bias. A time and cost analysis of participant retention efforts by Rdesinski et al showed spending approximately 1.2 hours and $39.14 per participant was required for a 90% retention rate in a population of young women of lower socioeconomic status and level of education [10]. In a contraceptive clinical trial, Macaluso et al found that attrition in their study biased results regarding health-related behaviors [11].…”
Section: Discussionmentioning
confidence: 99%
“…While extensive follow-up may improve participant retention, it can also be time consuming, costly, and may contribute bias. A time and cost analysis of participant retention efforts by Rdesinski et al showed spending approximately 1.2 hours and $39.14 per participant was required for a 90% retention rate in a population of young women of lower socioeconomic status and level of education [10]. In a contraceptive clinical trial, Macaluso et al found that attrition in their study biased results regarding health-related behaviors [11].…”
Section: Discussionmentioning
confidence: 99%
“…There is some data to suggest that in the context of these structural, psychological, and social factors, members of low-income communities are more likely to enroll in research studies if they are referred to them by a trusted resource, or the study is conducted through a known source or in the context of a familiar agencies (e.g., Women, Infants, and Children), neighborhoods (e.g., subsidized public housing, public schools), and local, state, and federal initiatives that families already use (e.g., Medicaid) (e.g., Rdesinski et al, 2008; Wallace, Berent, McCarthy, Senn, & Carey, 2014; Yancey et al, 2006). When surrounded by unfamiliar research staff, low-income families may be less likely to ask informed questions that would facilitate decision-making regarding participation in services research or to understand and/or adhere to research protocols, preventing them from benefiting from state-of-the-field advances in psychosocial services research (Schillinger, Bindman, Wang, Stewart, & Piette, 2004; Stewart et al, 1999).…”
Section: Optimize Recruitment Engagement and Retention Via Sensitivitymentioning
confidence: 99%
“…To some extent we know that this “match” occurs for some low incomes families, as those who have previously participated in research studies are more likely to participate in future research (Rdesinski et al, 2008). In addition, offering incentives, defined broadly here to include monetary compensation (e.g., $50/assessment), gift cards (e.g., accessible store or restaurant), meals (e.g., dinner for child and family), and educational materials (e.g., books) may increase the likelihood that low-income families report feeling more valued by researchers and, in turn, more likely to participate (e.g., Heinrich, 2006; Wallace et al, 2014; Yancey et al, 2006).…”
Section: Optimize Recruitment Engagement and Retention Via Sensitivitymentioning
confidence: 99%
“…5,7–13 Some researchers applying this knowledge to research engagement report success with the use of specific recruitment strategies for specific populations. 14–17 Others have undertaken systematic reviews of the literature on the topic and point to the effectiveness of community-based strategies including building relationships with community organizations and maintaining community interaction either through community advisory boards or other means. 1819 Indeed, there is a well established literature on community-based approaches.…”
mentioning
confidence: 99%
“…Moreover, community relationship building is intensive work that may be difficult for some projects. 17 Deep interpersonal relationships between participants and research staff are not feasible for all projects due to any number of reasons including limitations of time, resources, and staff. Thus, the practical implementation of community-based approaches is often reported as specific recommended strategies.…”
mentioning
confidence: 99%